Sensory Function, Measured as Active Discriminative Touch, is Associated With Dexterity after Stroke. Issue 8 (7th March 2019) - Carlsson, Håkan; Ekstrand, Elisabeth; Brogårdh, Christina
Abstract : Background: Reduced dexterity is common after stroke, which can affect the ability to perform upper limb daily activities. To improve upper limb function after stroke, it is important to understand which factors are most associated with dexterity. Objective: To evaluate how several factors are associated with dexterity after stroke. Design: Cross‐sectional study. Setting: A university hospital. Participants: A convenience sample of 75 persons (54 men and 21 women, mean age 66 years) with mild to moderate impairments of the upper limb after stroke. Methods: Dexterity and potentially associated factors (age, gender, affected hand, social situation, vocational situation, grip strength, spasticity, sensory function, and pain) were evaluated by linear regression models. Main Outcome Measurements: Dexterity was measured with the mini Sollerman Hand Function Test, sensory function with both the Fugl‐Meyer Assessment of the Upper Extremity (to assess light touch and proprioception) and the Shape Texture Identification Test (to assess active discriminative touch), spasticity with the Modified Ashworth Scale, and grip strength with the Grippit dynamometer. Results: Active discriminative touch had the strongest association with dexterity, explaining 46% of the variance. When spasticity and grip strength were added, the explained variance increased to 57% in the final multivariate model. Conclusions: This study indicates that sensory function in terms of active discriminative touch is a major contributing factor to dexterity in persons with mild to moderate stroke, whereas spasticity and grip strength may be of lesser importance. Level of Evidence: III